1994
DOI: 10.1177/1046496494254006
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Commitments Presupposed by Functional Approaches to Group Discussion

Abstract: Functional theory is theory in which the central core includes a description of attributes that lead to good consequencesfor, and/or that satisfy agoal of, a system or the system's designer or user. The application of functional theory to small group discussion requires the theorist to make two types of theoretical commitments. First, functional theories should include scientific functional explanations. Second, finctional theories should include a description of necessary discussionfunctions on one and only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…A functional approach to group communication assumes that interaction processes have utility and are the primary means by which members achieve group outcomes (Pavitt, 1994). Communication is functional in the sense that it accomplishes some long-or short-term ends that are not always evident from its content (Austin, 1962;Brown & Levinson, 1987;Grice, 1975;Searle, 1969;Watzlawick, Beavin, & Jackson, 1967).…”
Section: Functional Approaches To Group Communicationmentioning
confidence: 99%
“…A functional approach to group communication assumes that interaction processes have utility and are the primary means by which members achieve group outcomes (Pavitt, 1994). Communication is functional in the sense that it accomplishes some long-or short-term ends that are not always evident from its content (Austin, 1962;Brown & Levinson, 1987;Grice, 1975;Searle, 1969;Watzlawick, Beavin, & Jackson, 1967).…”
Section: Functional Approaches To Group Communicationmentioning
confidence: 99%
“…The functional theory of group decision making (Gouran & Hirokawa, 1996;Gouran, Hirokawa, Julian, & Leatham, 1993;Hirokawa & Scheerhorn, 1986;Mayer, 1998;Pavitt, 1994) explains how interactional norms formed in conflict situations can influence decision making, even when decisions do not involve conflict. Functional theory posits that "group interaction affects decision-making performance by directly shaping the quality of vigilance (or critical thinking) that leads to a final group choice" (Hirokawa & Rost, 1992, p. 269).…”
Section: Influence Of Conflict Management Styles On Decision-making Ementioning
confidence: 99%
“…17 Hirokawa's research was conducted to learn about the differences in group procedures when members make "good" and "bad" decisions, thus studying "best" and "worst" groups. 18 He concluded that members of the effective groups examined the validity of one another's opinions and assumptions; people in the more successful groups compared alternatives to a set of criteria they believed a good decision should meet; and both groups based their choices on premises. The premises of the successful groups followed directly from facts that the members possessed about each option and that the premises of the ineffective groups did not have a good basis in fact.…”
Section: March 1997mentioning
confidence: 99%